Aeromonas salmonicida subsp. salmonicida in the light of its type‐three secretion system. Issue 5 (7th October 2013) - Vanden Bergh, Philippe; Frey, Joachim
Summary Aeromonas salmonicida subsp. salmonicida is an important pathogen in salmonid aquaculture and is responsible for the typical furunculosis. The type‐three secretion system (T3SS) is a major virulence system. In this work, we review structure and function of this highly sophisticated nanosyringe in A. salmonicida. Based on the literature as well as personal experimental observations, we document the genetic (re)organization, expression regulation, anatomy, putative functional origin and roles in the infectious process of this T3SS. We propose a model of pathogenesis where A. salmonicida induces a temporary immunosuppression state in fish in order to acquire free access to host tissues. Finally, we highlight putative important therapeutic and vaccine strategies to prevent furunculosis of salmonid fish.